The Influence of Agile Leadership on Employee Work Motivation at the Regional Disaster Management Agency (BPBD) of West Sumatra Province - Ridhani Ikhsan; Syamsir Syamsir (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The high disaster risk in West Sumatra Province requires the Regional Disaster Management Agency (BPBD) to maintain an adaptive and motivated workforce; however, employees reportedly demonstrate limited initiative, dependence on top-down directives, and insufficient engagement in routine operational activities. Although agile leadership has been widely examined in private-sector and digital contexts, its relevance to public emergency organizations operating within rigid bureaucratic structures remains underexplored. This study aims to analyze the role of agile leadership in predicting employee work motivation at the BPBD of West Sumatra Province. A quantitative cross-sectional survey was conducted involving 56 respondents selected using the Slovin formula from a population of 64 employees. Data were collected through questionnaires and analyzed using descriptive statistics and simple linear regression. The findings indicate that the Respondent Achievement Rate for agile leadership was 69.07%, while work motivation reached 71.45%, with both variables categorized as high. Regression analysis produced the equation Y = 1.907 + 0.482X and demonstrated a statistically significant positive association between agile leadership and work motivation (p < .001). The coefficient of determination (R² = .254) indicates that agile leadership explained 25.4% of the variance in employees’ work motivation, whereas 74.6% was attributable to factors not included in the model. Given the cross-sectional design, these findings establish predictive association rather than direct causality. The study contributes to public-sector leadership research by extending the application of agile leadership to a bureaucratic disaster-management context and implies that strengthening leaders’ openness to feedback, particularly the humble dimension, may enhance employee participation, autonomy, and motivation.